Etos Kerja Islami Pada Keberhasilan Usaha Pedagang Etnis Arab di Pasar Ampel Surabaya - Aziz Maulana Akhsan (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aimed to find out in depth the culture of Islamic work ethic in Arab Muslim traders in Pasar Ampel, Surabaya, as well as the impact of the implementation of Islamic work ethic on the success of their business. This research used qualitative methods and case studies as the strategy. Data collection was carried out by interviewing and observing research subjects directly. The study involved five traders as data sources. Qualitative explanatory was used as an analytical technique by explaining the results of interviews and direct field observations. The results of this study showed that, 1) in general, the understanding of the work ethic of Arab Muslim traders in Pasar Ampel Surabaya was in accordance with the characteristics of Islamic work ethic. However, in terms of practice or implementation, not all were in accordance with the characteristics of the Islamic work ethic, especially most of them did not have creativity, orientation to the future, and mental readiness to compete, so their efforts tended to be conservative. 2) Traders who had an understanding and practice that was in accordance with the characteristics of the Islamic work ethic experienced business success in the business they run